2014
DOI: 10.4028/www.scientific.net/msf.775-776.261
|View full text |Cite
|
Sign up to set email alerts
|

Izod Impact Tests in Polyester Matrix Composites Reinforced with Banana Fibers

Abstract: Polymer matrix composites have been applied in components such as helmets and shielding for which toughness is a major requirement. A natural fiber presents interfacial characteristics with polymeric matrices that favor a high impact energy absorption by the composite structure. The objective of this work was then to assess the Izod impact resistance of polymeric composites reinforced with different amounts, up to 30% in volume, of a promising high strength natural fiber, the banana fiber. The results showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Banana fiber (Musaceae family), illustrated in Fig.1, with average diameter of 0.2 mm could reach tensile strength higher than 700 MPa. Other investigations on the strength of banana fiber had already revealed significant results [11,12]. These reported results have shown that polymer composites reinforced with banana fibers present very interesting potential improvement.…”
Section: Introductionsupporting
confidence: 48%
“…Banana fiber (Musaceae family), illustrated in Fig.1, with average diameter of 0.2 mm could reach tensile strength higher than 700 MPa. Other investigations on the strength of banana fiber had already revealed significant results [11,12]. These reported results have shown that polymer composites reinforced with banana fibers present very interesting potential improvement.…”
Section: Introductionsupporting
confidence: 48%
“…Recent works on the impact resistance of thermoset polymer composites reinforced with long and aligned lignocellulosic fibers [10][11][12][13][14][15], revealed a much higher value for the impact energy. In particular, a polyester composite reinforced with 40% of curaua fiber reached 170 J/m [11], which is more than three times the maximum obtained by any short-cut and randomly oriented lignocellulosic fiber composites [9]. This remarkable result served as motivation for a work to confirm it with a different impact method, the Charpy test.…”
Section: Introductionmentioning
confidence: 69%
“…Hemp is one the lignocellulosic fiber with least knowledge as far as mechanical properties are concerned. Characterizations of these composites are being carried out for different polymer matrices and mechanical tests [12][13][14][15][16][17][18][19][20][21][22]. However, no tensile characterization was done so far for polymer composites reinforced with hemp fibers.…”
Section: Introductionmentioning
confidence: 99%